Estimating Social Preferences and Gift Exchange at Work - DellaVigna, Stefano; List, John A.; Malmendier, Ulrike; Rao, Gautam (American Economic Review, 2022)
We design three field experiments to estimate how workers' social preferences toward their employer motivates their work effort. We vary the pay rates offered to workers, the return to the employer, and employer generosity demonstrated via unexpected gifts. Workers exert effort even without private incentives, but their effort is insensitive to the return to the employer. This is consistent with “warm glow” but not pure altruism. The gifts have no effect on productivity, but engender extra work. This difference is explained partly by the finding that extra work is much more responsive to incentives than is productivity. (JEL C93, J24, J28, J33, M52)